Phenol-soluble modulin contributes to the dispersal of Staphylococcus epidermidis isolates from catheters - Jin, Yixin; Wang, Qichen; Zhang, Haomin; Zhao, Na; Yang, Ziyu; Wang, Hua; Li, Min; Liu, Qian (Frontiers in Microbiology, 2022)
Staphylococcus epidermidis (S. epidermidis), a human commensal, has been implicated in invasive infection in humans due to their ability to form biofilm. It is assumed that when a biofilm is dispersed it will subsequently cause a more severe infection. The clinical significance of S. epidermidis isolated from sterile body fluid (BF) remains unclear, and might be related to dispersal from catheter-associated biofilm infection. To evaluate this relationship, we evaluated S. epidermidis isolates from catheters (CA) or BF in hospitalized patients. Sequence type 2 (ST2) is the most prevalent type isolated from infection sites. Although the specific STs were also observed in isolates from different sites, we observed that the main sequence type was ST2, followed by ST59, among all the 114 isolates from different infection sites. Interestingly, ST2 strains isolated from BF exhibited significantly thicker biofilm than those from CA. The thicker biofilm was due to the higher expression of accumulation-associated protein (aap) but not intercellular adhesion (ica) operon. Moreover, the transcription of PSMδ and PSMε were significantly increased in ST2 strains isolated from BF. Although the bacterial loads on catheters were similar infected by CA- or BF-originated strains in mouse biofilm-associated infection model, we observed a higher CFU in peri-catheter tissues infected by ST2 clones isolated from BF, suggesting that S. epidermidis with thicker biofilm formation might be able to disperse. Taken together, our data suggested that S. epidermidis originated from diverse infection sites exhibited different biofilm forming capacity. The major ST2 clone isolated from BF exhibited thicker biofilm by increasing the expression of Aap. The higher expression of PSM of these strains may contribute to bacteria dispersal from biofilm and the following bacterial spread.